Assessing Worldwide Research Activity on ICT in Climate Change Using Scopus Database: A Bibliometric Analysis - Stefanis, Christos; Giorgi, Elpida; Kalentzis, Konstantinos; Tselemponis, Athanasios; Tsigalou, Christina; Nena, Evangelia; Kontogiorgis, Christos; Kourkoutas, Yiannis; Voidarou, Chrysa; Chatzaki, Ekaterini; Dokas, Ioannis; Konstantinidis, Theodoros; et al. (Frontiers in Environmental Science, 2022)
Internet and Communication Technology tools have been already introduced in every aspect of environmental science. Regarding climate change, research trends and developments on ICT help realize how ICT evolved and its potential future role in climate change. This research aimed to assess ICT solutions in climate change trends using the Scopus database, bibliometric indicators, and network visualization. After a preliminary application of various combinations, the phrase 'ICT and climate change' was used with language selection "English" from 01/01/1999 to 01/12/2021. A collection of 453 articles published in scientific journals and conference proceedings was revealed, which allowed the visualization mapping of the research agenda in the field of ICT and climate change. The most relevant topics are related to Computer Science, Engineering, Environmental and Social sciences. It has been found that a significant amount of documents were published after 2008. The Royal Institute of Technology-KTH was the most productive institution, followed by the Consiglio Nazionale Delle Ricerche and the Universitetet I Oslo. In addition, the dominant countries in the respective research area were the United Kingdom, Italy, USA, India and Sweden. According to citations, most of the published research activity emerged in various journals, like Environment and Planning, Cities and Energies. It was possible to spot past trends and ongoing development, intending to introduce ICT tools in climate change impacts and examine the issues expected to be pertinent in the future.